2011
DOI: 10.1021/ci2000264
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Neurokinin B and Tachykinin NK3 Receptor Complex

Abstract: The tachykinin receptor NK₃ is a member of the rhodopsin family of G-protein coupled receptors. The NK₃ receptor has been regarded as an important drug target due to diverse physiological functions and its possible role in the pathophysiology of psychiatric disorders, including schizophrenia. The NK3 receptor is primarily activated by the tachykinin peptide hormone neurokinin B (NKB) which is the most potent natural agonist for the NK₃ receptor. NKB has been reported to play a vital role in the normal human re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Each copper hyperfine resonance will be split into 2nI + 1 (I = 1) resonances from coupling to a number (n) of magnetically equivalent nitrogen nuclei. These resonances will also have a characteristic intensity pattern, for example, coupling to four magnetically equivalent nitrogen nuclei will result in nine 14 N hyperfine resonances with an intensity pattern of (1: Table 1 yields the second derivative spectrum in blue ( Figure 5c 4 ] center and suggests the presence of a neutral species, which is consistent with the lack of a peak in the mass spectrum.…”
Section: ■ Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Each copper hyperfine resonance will be split into 2nI + 1 (I = 1) resonances from coupling to a number (n) of magnetically equivalent nitrogen nuclei. These resonances will also have a characteristic intensity pattern, for example, coupling to four magnetically equivalent nitrogen nuclei will result in nine 14 N hyperfine resonances with an intensity pattern of (1: Table 1 yields the second derivative spectrum in blue ( Figure 5c 4 ] center and suggests the presence of a neutral species, which is consistent with the lack of a peak in the mass spectrum.…”
Section: ■ Resultsmentioning
confidence: 62%
“…These peaks are characteristic of an α-helical structure, which is consistent with previous structural studies and is thought to be a physiologically relevant state. 4,37,38 The addition of 0.5, 1.0, and 1.5 equiv of copper results in a loss of intensity of all peaks, and a plot of the absolute intensity of the negative peaks as a function of the copper equivalents added shows that copper addition beyond 0.5 equiv has little effect on the intensity ( Figure 6B). In accord with the visible CD and electronic absorption spectroscopy, this confirms a stoichiometry of 1:2 Cu II /NKB.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Notably, the TM3, TM6 and TM7 domains of TACR3s, which have been demonstrated to be critical for ligand recognition in mammals (Gether et al, 1993), are highly conserved in zebrafish and human. The residues (N138, N142, Y315, F342, and M346) in human TACR3 are considered to be important for NKB binding (Ganjiwale et al, 2011;Malherbe et al, 2008), and these residues are also found to be located in the zebrafish TACR3s according to their homologous positions on human TACR3 (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…The signature motif in tilapia was different from that of all other fish examined (Figure 1). The C-terminal motif of NKBs is important to the binding of NKBs to their cognate receptors (32). We further searched for NKB of other cichlids.…”
Section: Identification Cloning Phylogenetic Analyses and Synteny mentioning
confidence: 99%